2022
DOI: 10.3390/ani12182378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic or Inorganic Mineral Premix in the Diet on Laying Performance of Aged Laying Hens and Eggshell Quality

Abstract: In this study, we examined the effect of diets supplemented with organic and inorganic mineral premixes on the laying performance and eggshell quality of aged laying hens. A total of 600 68-week-old Hy-Line Brown laying hens were randomly assigned to 1 of 3 dietary treatments, repeated 5 times: Mash type basal diet, basal diet supplemented with an inorganic mineral premix (1.0 g/kg), and basal diet supplemented with an organic mineral premix (1.8 g/kg). The results showed that eggshell strength was higher (p &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Khoshbin, Vakili, and Tahmasbi [14] found that feeding late-lay hens a 50/50 or 25/75 ratio of MnSO 4 and AAC Mn increased hen day egg production and egg mass compared to feeding 100% inorganic Mn. Overall, the results of this experiment agree with several previous studies in late-phase laying hens in which feeding AAC or sulfated minerals did not affect egg production [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Khoshbin, Vakili, and Tahmasbi [14] found that feeding late-lay hens a 50/50 or 25/75 ratio of MnSO 4 and AAC Mn increased hen day egg production and egg mass compared to feeding 100% inorganic Mn. Overall, the results of this experiment agree with several previous studies in late-phase laying hens in which feeding AAC or sulfated minerals did not affect egg production [15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…Although some of the diets contained some Zn or Mn from both sources, there were no differences in egg shell quality between treatments. Kim et al [16] found no effect of mineral source on egg shell mineral content. Furthermore, Zhang et al [19] found no change in egg shell mineral content from late-phase laying hens fed any combination of AAC and sulfated trace minerals compared to those fed only sulfated minerals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The practical experience of scientists has revealed that an increase in the productivity of broiler chickens is possible when creating an optimal food base that provides birds with all nutrients and biologically active substances needed for the complete realization of their genetic potential [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%